Salman Rushdie's concept of wholeness in the context of the literature of India - Manecke, Ute (2006)
Why is it worthwhile to explore the concept of wholeness? One answer to this question is that wholeness is something we are all striving for and thus seems to be of central importance in our lives. Although we sometimes use different words to describe what we mean by wholeness, our alleged synonyms or descriptions all tend to emphasise the positive meaning associated with it. One specific synonym, unbroken, shows particularly well these positive associations. For a long time many people have believed in the myth that we were once whole, but lost our wholeness and should now endeavour to retrieve it.1 A reason why this is desirable is that something that is united and not fragmented is usually in the position to function as it should. In human beings, the capability to function properly can only be generated when the individual meets adequate standards of health and well-being. In fact, there has now emerged the term wholistic originally spelled holistic - health, which is defined as whole person health or simply as wellness ...
Erscheinungsjahr an der Haupttitelstelle: 2005
Keywords: Rushdie, Salman -- 1947-; Indien; Hochschulschrift; Ganzheit; Identität; Rushdie, Salman